The influence of exercise-induced plasma volume changes on the interpretation of biochemical parameters used for monitoring exercise, training and sport - Kargotich, S.; Goodman, C.; Keast, D.; Morton, A. R. (Sports Medicine, 1998)
A number of studies have demonstrated considerable plasma volume changes during and after exposure to different environmental and physiological conditions. These changes are thought to result from transient fluid shifts into (haemodilution) and out of (haemoconcentration) the intravascular space. If the levels of plasma constituents are to be routinely measured for research purposes or used as indicators of training adaptation or the health of an athlete, then it is important to consider the dynamic nature of plasma volume. Controversy still exists over the relevance of plasma volume interactions with plasma constituent levels, and while some investigators have taken plasma volume shifts into account, others have chosen to ignore these changes. Bouts of acute exercise have been shown to produce a transient haemoconcentration immediately after long distance running, bicycle ergometry and both maximal and submaximal swimming exercise. While these changes are transient, lasting only a few hours, other studies have reported a longer term haemodilution following acute exercise. In addition, endurance training has been shown to cause long term expansion of the plasma volume. It would, therefore, seem important to consider the influence of plasma volume changes on plasma solutes routinely measured for research, and as markers of training adaptation,prior to arriving at conclusions and recommendations based purely on their measured plasma level. To further confound this issue, plasma volume changes are known to be associated with heat acclimatisation, hydration state, physical training and postural changes, all of which may differ from one experiment or exercise bout to the next, and should thus be taken into account.